Effect of Thermocycling on Surface Roughness and Shear Bond Strength of Acrylic Soft Liner to the Surface of Thermoplastic Acrylic Treated with Ethyl Acetate - Duha Qais Sabah; Bayan S. Khalaf (Indian Journal of Forensic Medicine & Toxicology, 2022)
Objective: To enhance bonding strength between thermoplastic denture base and acrylic soft liner through ethyl acetate surface treatment.Materials and Methods: Modifications of thermoplastic acrylic denture base surface were investigated with SEM. FTIR was used to detect whether there was a chemical bond between thermoplastic acrylic and the organic solvent. A total of 80 samples were prepared and divided into 20 samples for the surface roughness test and 60 samples for the shear bond strength test. Failure type was assessed visually.Results: Shear bond strength and surface roughness values of un treated samples were lower in comparison to surface treated groups; the greatest post thermocycling bond strength value was recorded for the samples treated with ethyl acetate following 1500 cycles.Conclusions: Bonding strength was improved following ethyl acetate surface treatment.